The Macrophage: A Disputed Fortress in the Battle against Mycobacterium tuberculosis - Queval, Christophe J.; Brosch, Roland; Simeone, Roxane (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis (Mtb), the etiological agent of human tuberculosis (TB), has plagued humans for thousands of years. TB still remains a major public health problem in our era, causing more than 4,400 deaths worldwide every day and killing more people than HIV. After inhaling Mtb-contaminated aerosols, TB primo-infection starts in the terminal lung airways, where Mtb is taken up by alveolar macrophages. Although macrophages are known as professional killers for pathogens, Mtb has adopted remarkable strategies to circumvent host defenses, building suitable conditions to survive and proliferate. Within macrophages, Mtb initially resides inside phagosomes, where its survival mostly depends on its ability to take control of phagosomal processing, through inhibition of phagolysosome biogenesis and acidification processes, and by progressively getting access to the cytosol. Bacterial access to the cytosolic space is determinant for specific immune responses and cell death programs, both required for the replication and the dissemination of Mtb. Comprehension of the molecular events governing Mtb survival within macrophages is fundamental for the improvement of vaccine-based and therapeutic strategies in order to help the host to better defend itself in the battle against the fierce invader Mtb. In this mini-review, we discuss recent research exploring how Mtb conquers and transforms the macrophage into a strategic base for its survival and dissemination as well as the associated defense strategies mounted by host.